John Henry : Roark Bradford's Novel and Play. - Tracy, Seven C. (Oxford University Press, USA, 2008)
Introduction. Bibliography for introduction. Discography of recordings echoing the folk tradition in the novel. Transcriptions of versions of the folk songs. John Henry folk song bibliography. John Henry bibliography, 1932-Present. John Henry folk song discography, 1921-1931. Roark Bradford Bibliography. Reviews of the novel. Reviews of the play. Roark Bradford Chronology. John Henry: the novel _. I. The Birth of John Henry. II. Coonjine. III. The Black River Country. IV. V. VI. Back of Town. VII. Julie Anne. VIII. Fourteen-Thirty-Six. IX. Woman on My Weary Mind. X. Poor Selma. XI. Stacker Lee.